Behavior of Schistosoma mansoni-induced histopathological lesions in Biomphalaria glabrata submitted to ionizing radiation - Azevedo Carine M.; Borges Claudia Cunha; Andrade Zilton A. (Sociedade Brasileira de Medicina Tropical (SBMT), 2004)
Present report demonstrates that repeated radiation of Schistosoma mansoni-infected Biomphalaria glabrata, totaling 15,000 rads, caused a sudden, albeit transient, suppression of cercarial shedding. Initially, sporocysts practically disappeared from the snail tissues. The more resistant developing cercariae presented nuclear clumping and vacuolation, before undergoing lysis. No host tissue reaction was evident at any time. Thirty-four days after the last irradiation, the snails resumed cercarial elimination. By that time numerous sporocysts and developing cercariae were detected, disseminated throughout snail tissues in a pattern similar to that of a highly malignant neoplasm, with no signs of host cellular reactions, which on the other hand were present in non-irradiated infected controls. The region of the ovo-testis was apparently destroyed after radiation, but returned to its normal appearance around 40 days after the last radiation. Ionizing radiation affected both host and parasite in S. mansoni-infected Biomphalaria glabrata, but the resulting impressive changes were soon reversed.